Isolation and Characterization of Endophytic Bacteria from Tembelekan (Lantana camara L.) as Antibacterial Compounds Producer - Dina Dyah Saputri; Maria Bintang; Fachriyan H Pasaribu (Current Biochemistry, 2015)
Endophytic bacteria are microorganisms that live in the internal tissues of plants and have symbiotic mutualism with their host plants. Endophytic bacteria may produce secondary metabolites that can be developed for medical, agricultural, and industrial purposes. Lantana camara is a medicinal plant that has therapeutic potential to treat a variety of diseases such as fever, tuberculosis, rheumatism, asthma, and skin disease. The purpose of this study was to isolate and characterize endophytic bacteria from Lantana camara which has potential to produce antibacterial compounds. The method of this research include isolation of endophytic bacteria of Lantana camara. Antibacterial activity assay was done against four types of pathogenic bacteria i.e. Bacillus cereus, Escherichia coli, Staphylococcus aureus, and Salmonella enteritidis. Characterization of endophytic bacteria was by 16S rRNA gene analysis and identification of antibacterial compounds by GC-MS analysis. Isolation of endophytic bacteria from Lantana camara resulted in BT22 as a potential isolate. Analysis of 16S rRNA gene showed that the BT22 isolate was similar to Bacillus amyloliquefaciens YB-1402 with 99% identity. The results of GC-MS analysis showed some antibacterial compounds such as: Cyclohexanone, 2-[2-(1,3-dithiolan-2-yl)propyl]-6-methyl-3-(1-methylethyl), Octadecane (CAS) n-Octadecane and Tetracosane (CAS) n-Tetracosane.